Prefibrillar Tau Oligomers in MCI and Alzheimer Disease - Mufson, Elliott J. (2013)
BACKGROUND: AD (Alzheimer’s disease) is a progressive neurodegenerative disorder characterized by the accumulation of extracellular amyloid β-peptide and intracellular tau. Here we review data suggesting that pre-fibrillar tau oligomers mediate cognitive decline early in the disease. OBJECTIVE: To study the presence of tau-positive pre-tangle neurons and correlate findings with cognitive test scores. METHODS: Pre-tangle antibodies (TOC1 and pS422) were applied to tissue containing cholinergic basal forebrain neurons from people who died with a pre-mortem clinical diagnosis of no cognitive impairment, mild cognitive impairment and AD. RESULTS: Data lend support to the concept that tau oligomers are the toxic form of tau, that non-fibillar tau relates to cognitive dysfunction and that the earliest pretangle pathology occurs in neuritic processes. CONCLUSIONS: Clinicopathological findings highlight the importance of studying tau modifications in neuronal soma and neuritic processes, which may be the earliest pathological lesions, which correlate with cognitive status.